Value of two mortality assessment techniques for organ cultured corneal endothelium: trypan blue versus TUNEL technique. Issue 3 (1st March 2002) - Gain, P; Thuret, G; Chiquet, C; Dumollard, J M; Mosnier, J F; Burillon, C; Delbosc, B; Hervé, P; Campos, L
Abstract : Background/aim: It is known that trypan blue staining is not a good predictor of loss of corneal endothelial cells (ECs) during organ culture. As it is primarily an indicator of membrane integrity, it would also not be expected to identify ECs undergoing apoptosis. The aim of this study was to determine the ability of the in situ TdT dUTP mediated nick end labelling (TUNEL) technique to detect cell death in the corneal endothelium caused by apoptosis during organ culture, compared with conventional vital staining with trypan blue. Methods: 31 human corneas were organ cultured at 31°C for 3–35 days. Staurosporine was used to induce apoptosis in five control corneas. The endothelium was assessed by trypan blue and by the in situ TUNEL technique. The percentages of trypan and TUNEL positive ECs were compared. Their links with sex, donor age, time from donor death and organ culture, initial and final EC density and cell loss were studied. Results: TUNEL stained ECs were observed in all corneas. TUNEL positive ECs were mostly located either in corneal folds or at the periphery of corneal folds showing central shedding. The mean percentage of cell death at the end of storage, assessed by the trypan blue technique, was 1.47% (SD 2.63, range 0.03–12); assessed by the TUNEL technique it was 12.7% (SD 16.4 range 0.6–65.5). There was a significant correlation between the two techniques ( r = 0.7, p<0.001). The percentage of TUNEL stained ECs was correlated negatively with EC density at the end of storage ( r = −0.47, p <0.005) and positively with percentage EC loss during storage ( r = 0.46, p < 0.05). Conclusion: This study demonstrates that organ cultured corneas systematically carry non-viable ECs that are implicated in cell death by apoptosis and go undetected when trypan blue staining is used. Because the in situ TUNEL assay detects earlier events in the cell death process than does trypan blue, it should be used to quantify endothelial viability, especially for experiments with new storage media.